Mindfulness and Cognitive Training in a CBT-resistant Patient With Gambling Disorder: A Combined Therapy to Enhance Self-control. Issue 6 (November 2018) - von Hammerstein, Cora; Miranda, Ruben; Aubin, Henri-Jean; Romo, Lucia; Khazaal, Yasser; Benyamina, Amine; Luquiens, Amandine
Abstract : N/A: Despite the major health consequences of problem gambling, such as suicide, over-indebtedness, delinquency, or family problems, there is currently no approved drug available for the treatment of problem gambling. The efficacy of cognitive behavioral therapies (CBTs) has been demonstrated repeatedly. However, some people seem resistant to conventional CBT alone. We present the case of a 59-year-old woman with a gambling disorder, who relapsed, despite a CBT-based intervention, and who then received a combined therapy aiming to enhance self-control: a mindfulness-based therapy and cognitive training targeting inhibition.